Analisi Pengaruh Knowledge Management pada pengaruh Konflik Peran Ganda terhadap Kinerja Wirausaha Wanita - Ris Akril Nurimansjah; Mursida Mursida; Muhammad Zadli Syahdi (Paser Institute Management and Busines, 2023)
This research aims to determine the influence of dual role conflict and knowledge management on the performance of women entrepreneurs in Palopo City. This type of research is survey research using a multiple liner regression model. the population in this study are women entrepreneurs, especially the MSME sector in the city of Padang. This study used a purposive sampling technique with random sampling. Secondary data in this research was obtained from the Department of Cooperatives and UMKM of Palopo City, while primary data in this research was obtained from a questionnaire distributed to the research sample which contained questions about indicators that influence dual role conflict and knowledge management on the performance of women entrepreneurs. The results of this study indicate that multiple role conflict has an effect and is significant on the performance of women entrepreneurs. Knowledge management has no significant effect on the performance of women entrepreneurs. Multiple role conflict and knowledge management on the performance of women entrepreneurs.